DEVELOPING STUDENTS' SCIENTIFIC KNOWLEDGE THROUGH TEACHING THE SUBJECT 'HISTORY OF UZBEKISTAN (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the issue of developing students' scientific knowledge through the teaching of the subject “History of Uzbekistan.” It highlights the role of modern pedagogical technologies in promoting deep understanding of historical knowledge, independent thinking, and scientific research skills. The necessity of viewing the “History of Uzbekistan” not merely as a set of historical facts but as a key factor in the development of analytical and critical thinking is substantiated. The article also examines the possibilities of shaping students’ historical thinking through the vitagenic approach, educational situations, interactive methods, and innovative teaching tools. The research findings show that this subject can significantly enhance students’ scientific worldview and research potential.